Machine learning and data mining in pattern recognition : 11th International Conference, MLDM 2015, Hamburg, Germany, July 20-21, 2015, Proceedings /: 11th International Conference, MLDM 2015, Hamburg, Germany, July 20-21, 2015, Proceedings. (2015) - Unknown
No abstract available